2000
DOI: 10.1097/00005768-200011000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of compression hosiery on physiological responses to standing fatigue in women

Abstract: Wearing various types of graduated compression hose during the day as it relates to women in standing professions may minimize edema and muscle tissue disruption, thereby increasing comfort in the legs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 21 publications
2
79
1
5
Order By: Relevance
“…The computer use group showed statistically significant differences in the upper trapezius and the smartphone use group showed statistically significant differences in the brachioradialis when compared with the control group (p<0.05). In general, muscle fatigue is caused by work that requires repeated movement in static postures, and thus the median frequency of muscles also gradually decreases 21) . The decreases in median frequencies that appeared in the results of the current study showed that the use of smartphones and computers requiring repeated motions induced upper extremity muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The computer use group showed statistically significant differences in the upper trapezius and the smartphone use group showed statistically significant differences in the brachioradialis when compared with the control group (p<0.05). In general, muscle fatigue is caused by work that requires repeated movement in static postures, and thus the median frequency of muscles also gradually decreases 21) . The decreases in median frequencies that appeared in the results of the current study showed that the use of smartphones and computers requiring repeated motions induced upper extremity muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…From 1996 until 2001 [11,[20][21][22][23], systematic research on various types of compression shorts with Lycra elastic fibres was conducted (Table 2). According to the results, it was found that compression shorts did not have a special effect on the single maximum ground reaction force or maximum power compared with normal sports shorts.…”
Section: Compression Garments and Strength Performancementioning
confidence: 99%
“…Optimal compression also allows the body structures to be held in place reducing the amount of movement and oscillation upon contact or allows limbs to be kept in anatomical positions when not used allowing straight-line tissue repair geometrics (19,20). Compression has also been linked to enhancing the ''muscle pump'' allowing blood return to the heart for removal of waste products (3,27). Finally, mechanical support is needed when added force is required for a movement, and this seems possible only with high compression and material mechanics not optimal for anything but short-term use (39).…”
Section: Introductionmentioning
confidence: 99%